Video-mediated drawing interventions for enhancing spatial cognition among young children - Prayitno, Prayitno; Hendri, Zulfi; Arifiyanti, Nurul; Syamsudin, Amir; Triawan, Denny Wahyu; Putri, Rachmalia Sinta Andika; Hardiyanti, Widya Dwi (Journal of Interdisciplinary Studies in Education, 2026)
Visual–spatial skills are foundational cognitive competencies that support young children’s academic achievement, particularly in mathematics and reading comprehension. However, their integration into early childhood instructional practice remains limited. This study examined the effectiveness of a video-guided drawing intervention in enhancing preschool children’s visual–spatial ability. A preexperimental one-group pretest–posttest design was used with 65 children aged 5–6 years. Teachers received structured training to ensure consistent implementation of the intervention. Visual–spatial ability was measured using a validated drawing rubric to assess object form accuracy, compositional organization, and color application. Data were analyzed using normality and homogeneity tests followed by a paired-samples t test (α = 0.05). The results indicated a significant improvement in visual–spatial abilities following the intervention (mean difference = −1.600, SD = 1.235), t(64) = −10.446, p < 0.001, with a 95% confidence interval of −1.906 to −1.294, indicating a large effect size. These findings suggest that video-guided drawing is an effective strategy for enhancing visual–spatial skills and support the integration of interactive video-based approaches in early childhood curricula.